Importance of medical and social factors in etiology of oral diseases of children - Yariyeva Oynisa Oltinovna (Genius Publishing Group, 2021)
Dental diseases are the most common diseases in relation to other pathologies observed in the human body and damage to the hard tissue of the teeth - caries ranks first in frequency of occurrence. According to the results of epidemiological studies, the spread of caries varies from 70 percent to 90 percent and now there is no trend of decreasing. In addition, according to some authors [1]. Despite the fact that recently active preventive and curative procedures are underway, it’s observed growth of disease rate day by day
Keywords: Oral diseases; teeth - caries; damage